DYNAMIZATION PERFORMANCE OF THIRTEEN WHEAT GENOTYPES DURING THREE PLANTING SEASON FOR ADAPTATION IN TROPICAL LOWLAND - Nugraheni Widyawati; Theresa Dwi Kurnia; Djoko Murdono (AGRIVITA, Journal of Agricultural Science, 2015)
The successful development of wheat in several tropical highlands in Indonesia has prompted researchers to developing the wheat in the lowlands area. One of the ways is through the process of adaptation and selection of wheat genotypes which planted in lowlands. This research was conducted in the district of Semarang and Demak in the period of 2011 until 2014. The purpose of this research was to investigate the performance of wheat genotypes grown in the tropical lowlands in searching the candidates for adaptive varieties of tropical lowland. Thirteen wheat genotypes that tested in the lowlands were ‘LAJ3302/2*M088’, ‘Altar’, ‘Selayar’, ‘Oasis’, ’HP1744’, ‘RABE’, ’H-21’, ‘G-21’, ‘G-18’, ‘Menemen’, ‘Barisbey’, ‘Alibey’, ‘Dewata’. The experimental design used was Randomised Block Design, treated separately with 13 genotypes, each genotype repeated 3 times. The data were analyzed using Analysis of variance, Correlation, HSD 5% level and Stress Susceptibility Index. The results of this research were the genotypes LAJ3302/2*M088, Oasis and Selayar has been considered as candidate of wheat varieties which adaptive in tropical lowland because this genotypes are more tolerant than the other genotypes in lowland environment.